Answer:
Step-by-step explanation:
By definition, the average rate of change of a function f over an interval [a,b] is given by

compute the quantity

for all the three function
Average rate of change of f:
We will simply use the table to check the values for f(3) and f(0):

Average rate of change of g:
We will use the graph to to check the values for g(3) and g(0):

Average rate of change of h:
We can plug the values in the equation to get h(3) and h(0):

And so the average rate of change is

Answer:
y=-4x-2
Step-by-step explanation:
linear function, y = mx+c
the y intercept of the graph,c, is -2
thus y = mx - 2
substitute a point on the graph into the equation, (2,-1)
2 = m(-1) -2
m = - 4
thus equation of graph is y = -4x-2